Analisis Kepuasan Pelanggan Nappa Milano Dikaji dari Pengaruh Kualitas Produk dan Layanan - Anggriani, Nurvita; Widiati, Euis (Jurnal MANAJERIAL, 2024)
This study intends to define customer satisfaction, elucidate product and service quality, and assess the impact of e-service and product quality on customer satisfaction with Nappa Milano. In order to collect data for this study, 100 respondents were given questionnaires, which were then analyzed using IBM SPSS version 23 and Excel. Quantitative descriptive analysis, multiple linear regression, hypothesis testing, and coefficient of determination were the analysis techniques employed. These findings demonstrate the strong impact that the factors of Product Quality and E-Service Quality have on customer satisfaction at Nappa Milano.